Corporate risk-taking behaviour: Corporate governance perspective - Dewanta, Aryestantya Fikri; Arifin, Johan (Journal of Contemporary Accounting, 2020)
This study examines the effect of corporate governance which represented by the board of directors, audit committee, managerial compensations, and ownership concentration toward corporate risk-taking behaviour in Indonesian manufacturing companies during the period of 2013-2017. Samples were collected using a purposive sampling method with a total of 69 companies, thus there were 345 observations over 5 years. Regression analysis shows that managerial compensations and ownership concentration positively affect corporate risk-taking. The members of the board of directors negatively affect corporate risk-taking. Meanwhile, the size of the audit committee does not significantly influence the company's risk-taking behaviour in manufacturing companies listed on the Indonesia Stock Exchange.